Severe adverse events by tyrosine kinase inhibitors decrease survival rates in patients with newly diagnosed chronic‐phase chronic myeloid leukemia. (23rd May 2018) - Ota, Shuichi; Matsukawa, Toshihiro; Yamamoto, Satoshi; Ito, Shinichi; Shindo, Motohiro; Sato, Kazuya; Kondo, Takeshi; Kohda, Kyuhei; Sakai, Hajime; Mori, Akio; Takahashi, Tohru; Ikeda, Hiroshi; et al.
Abstract: Objective: This multicenter cooperative study aimed to analyze the adverse events (AEs) associated with tyrosine kinase inhibitors (TKIs) used as initial treatment for chronic‐phase chronic myeloid leukemia (CML‐CP) and their impact on outcome. Methods: We retrospectively evaluated 450 patients with CML‐CP who received TKIs between 2004 and 2014. Results: The 5‐year overall survival (OS) and event‐free survival (EFS) rates were 95.1% and 89.0%, respectively. Patients with comorbidities (46.4%) and aged ≥60 years (50.4%) at diagnosis had significantly inferior OS to those without comorbidities and aged <60. Patients achieved higher rates of major molecular response (MMR) at 6 and 12 months after initial treatment with dasatinib or nilotinib compared to imatinib, but final MMR rates were almost the same. Sixty‐six percent of patients required treatment modifications from first‐line TKI therapy; the main reasons were AEs (48.4%) and failure (18%). Grade III‐IV AEs in first‐line TKI therapy were significantly correlated to inferior OS/EFS compared to grade 0‐II AEs. Conclusion: Although long‐term outcomes were similar in CML‐CP patients treated with each TKI regardless of first‐line TKI selection, severe AEs in first‐line TKI therapy decreased their survival rates. Early change in TKIs is recommended, when faced with severe AEs of specific TKIs.